Positive electrode material, secondary battery and electric device
By dispersing lithium manganese iron phosphate inside the hollow graphene coil, building a conductive network, solving the problems of insufficient conductivity and volume expansion of lithium manganese iron phosphate, improving the electrical performance and stability of the secondary battery, reducing internal resistance and production Gas risk.
Patent Information
- Application Number
- CN202411332072.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
AI Technical Summary
The conductivity of lithium manganese iron phosphate cathode material is poor, and volume expansion during charging and discharging causes the surface carbon layer to fall off, affecting the kinetic performance.
Lithium manganese iron phosphate is dispersed inside the hollow graphene coil, forming a conductive network through chemical action, improving the conductivity of electrons and ions, and using the hollow structure in the secondary battery to adapt to volume expansion and prevent separation.
It significantly improves the conductivity of the positive electrode material, reduces the internal resistance of the secondary battery, improves the stability of high and low temperature cycles and high temperature storage stability, and reduces gas production during the cycle.
Smart Images

Figure BDA0005058899740000121 
Figure BDA0005058899740000131 
Figure BDA0005058899740000132
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular to a positive electrode material, a secondary battery, and an electrical device. Background Art
[0002] Lithium-ion batteries have excellent charging and discharging performance, safety performance and recycling performance, and occupy a place in the new energy industry. At present, the positive electrode material of lithium-ion batteries, lithium iron phosphate, has evolved into lithium iron manganese phosphate material. Compared with lithium iron phosphate, lithium iron manganese phosphate has a higher voltage platform and a greater energy density, which ensures a higher endurance while taking into account the safety performance of lithium iron phosphate. However, the conductivity of lithium iron manganese phosphate itself is lower than that of lithium iron phosphate. Even if its utility is improved by coating the surface with a carbon layer, due to the volume expansion effect of lithium iron manganese phosphate itself during the charging and discharging process, the surface carbon layer is easy to fall off after a certain number of cycles, causing its dynamic performance to fail. Summary of the invention
[0003] The purpose of the present application is to solve the problem of poor conductivity of existing lithium manganese iron phosphate, and to provide a positive electrode material, a secondary battery, and an electrical device having excellent electronic and ionic conductivity, and when used in the preparation of secondary batteries, the obtained secondary batteries have excellent high and low temperature cycle stability, high temperature storage stability, low internal resistance and low cycle gas production.
[0004] To achieve the above objectives, in a first aspect of the present application, a positive electrode material is provided, wherein the positive electrode material comprises a hollow graphene roll and lithium iron manganese phosphate, wherein the lithium iron manganese phosphate is dispersed inside the hollow graphene roll.
[0005] As an embodiment of the present application, the positive electrode material satisfies: 11≤Y≤495;
[0006] Where, Y = d × S / σ;
[0007] d μm is the average inner diameter of the hollow graphene roll;
[0008] S m 2 / g is the specific surface area of the positive electrode material;
[0009] σ% is the oxygen content of the hollow graphene roll.
[0010] As an implementation scheme of the present application, 1≤d≤15.
[0011] As an implementation scheme of the present application, 10≤S≤250.
[0012] As an implementation scheme of the present application, 2≤σ≤10.
[0013] As an embodiment of the present application, the pore diameter of the positive electrode material is 1 to 280 nm.
[0014] As an implementation scheme of the present application, the mass ratio of the hollow graphene roll and the lithium iron manganese phosphate is hollow graphene roll: lithium iron manganese phosphate = 1: (9 to 99).
[0015] As an embodiment of the present application, the thickness of the hollow graphene roll is 1 to 10 nm.
[0016] As an embodiment of the present application, the lithium manganese iron phosphate satisfies 0.7 μm≤Dv50≤1.2 μm.
[0017] As an embodiment of the present application, the lithium manganese iron phosphate satisfies 0.2 μm≤Dv10≤0.3 μm.
[0018] As an embodiment of the present application, the lithium manganese iron phosphate satisfies 10 μm≤Dv90≤20 μm.
[0019] In a second aspect of the present application, a secondary battery is provided, comprising a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, and the positive electrode active material layer comprises the above-mentioned positive electrode material.
[0020] In a third aspect of the present application, an electrical device is provided, comprising the secondary battery described above.
[0021] Compared with the prior art, the beneficial effects of this application are:
[0022] In the positive electrode material provided by the present application, by dispersing lithium iron manganese phosphate inside the hollow graphene roll, the lithium iron manganese phosphate can interact with the hollow graphene roll through chemical reactions to jointly form a conductive network, which can effectively improve the electronic conductivity and ionic conductivity of the positive electrode material, thereby reducing the internal resistance of the secondary battery prepared subsequently and improving the electrical performance of the secondary battery; and, since the lithium iron manganese phosphate is dispersed inside the hollow graphene roll, when it is later used in a secondary battery, during the secondary battery cycle process, the hollow internal structure of the hollow graphene roll has enough space to accommodate the volume expansion of the lithium iron manganese phosphate, avoiding the separation of the hollow graphene roll and the lithium iron manganese phosphate as the cycle progresses, thereby effectively improving the high and low temperature cycle stability of the secondary battery and reducing gas production during the cycle; and due to the high stability of the positive electrode material, the obtained secondary battery also has good high temperature storage stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is an electron microscope observation image of the hollow graphene roll of this application;
[0024] Figure 2 This is an electron microscope observation image of ordinary flake graphene. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0026] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0027] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0028] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0029] In one embodiment of the present application, the present application proposes a positive electrode material, wherein the positive electrode material includes a hollow graphene roll and lithium iron manganese phosphate, wherein the lithium iron manganese phosphate is dispersed inside the hollow graphene roll.
[0030] The present application has studied and found that by dispersing lithium iron manganese phosphate inside the hollow graphene roll, the lithium iron manganese phosphate can interact with the hollow graphene roll through chemical reactions to form a conductive network, which can effectively improve the electronic conductivity and ionic conductivity of the positive electrode material, thereby reducing the internal resistance of the secondary battery prepared subsequently and improving the electrical performance of the secondary battery; and, since the lithium iron manganese phosphate is dispersed inside the hollow graphene roll, when it is later used in a secondary battery, during the cycle of the secondary battery, the hollow internal structure of the hollow graphene roll has enough space to accommodate the volume expansion of the lithium iron manganese phosphate, avoiding the separation of the hollow graphene roll and the lithium iron manganese phosphate as the cycle progresses, thereby effectively improving the high and low temperature cycle stability of the secondary battery and reducing the gas production during the cycle of the secondary battery; and due to the high stability of the positive electrode material, the obtained secondary battery also has good high-temperature storage stability.
[0031] In one embodiment, the positive electrode material satisfies: 11≤Y≤495;
[0032] Where, Y = d × S / σ;
[0033] d μm is the average inner diameter of the hollow graphene roll;
[0034] S m 2 / g is the specific surface area of the positive electrode material;
[0035] σ% is the oxygen content of the hollow graphene roll.
[0036] The research of the present application found that the electronic conductivity and ionic conductivity of the positive electrode material can be better improved by making the positive electrode material satisfy a specific relationship: 11≤Y≤495, and at the same time, the high temperature storage stability and high and low temperature cycle stability of the positive electrode material can be better improved; thus, when it is applied to the preparation of secondary batteries, the obtained secondary battery has lower internal resistance, better cycle performance, less gas production during the cycle, and better high temperature storage stability.
[0037] Exemplarily, the positive electrode material satisfies 11≤Y≤495, wherein Y may be any point value or any two point range values within the range of 11≤Y≤495, for example, Y may be 11, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, 300, 320, 340, 360, 380, 400, 420, 440, 460, 480, 495, etc.
[0038] In one embodiment, the positive electrode material satisfies 90≤Y≤160. For example, Y can be a range value of one or any two of 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160. The present application has found that when the positive electrode material is further selected to satisfy 90≤Y≤160, when the obtained positive electrode material is applied to the preparation of a secondary battery, the comprehensive performance of the obtained secondary battery is better.
[0039] In one embodiment, 1≤d≤15.
[0040] It should be noted that the average inner diameter d of the hollow graphene roll is obtained by scanning electron microscopy (SEM) testing, specifically SEM Figure 1 Average inner diameter of many graphene rolls within the calibration range.
[0041] The size of the average inner diameter of the hollow graphene roll will affect the chemical cross-linking strength between the hollow graphene roll and lithium iron manganese phosphate to a certain extent, and will also affect the coating effect of the hollow graphene roll on the lithium iron manganese phosphate, thereby affecting the high-temperature storage stability and high- and low-temperature cycle stability of the positive electrode material and the prepared secondary battery; and, since lithium manganese iron phosphate will produce trivalent manganese ions during the lithium deintercalation process, resulting in a strong John-Teller effect, which in turn causes lattice distortion and leads to volume expansion, the average inner diameter of the hollow graphene roll within a suitable range can avoid the problem of hollow graphene rolls peeling off from the periphery of lithium iron manganese phosphate due to volume expansion, thereby reducing the cycle stability of the secondary battery.
[0042] Exemplarily, d may be any point value or any two point range values in the range of 1≤d≤15, for example, d may be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, etc.
[0043] In one embodiment, 5.5≤d≤8.5. For example, d can be a range of one or any two of 5.5, 5.7, 5.9, 6.1, 6.3, 6.5, 6.7, 6.9, 7.1, 7.3, 7.5. The present application has found that when d is further selected to be 5.5≤d≤8.5, the overall performance of the obtained positive electrode material and the corresponding secondary battery prepared are better.
[0044] In one embodiment, 10≤S≤250.
[0045] It should be noted that the specific surface area of the positive electrode material is obtained by referring to the gas adsorption BET method test of GB / T19587-2017.
[0046] The specific surface area of the positive electrode material will affect the ionic conductivity and electronic conductivity of the positive electrode material itself to a certain extent, and will also affect the current density and degree of side reactions during charging and discharging of the prepared secondary battery, thereby affecting the internal resistance and cycle stability of the secondary battery and the gas production during the cycle.
[0047] Exemplarily, the S may be any point value or any two point range values in the range of 10≤S≤250, for example, S may be 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 120, 140, 160, 180, 200, 220, 240, 250, etc.
[0048] In one embodiment, 40≤S≤75. For example, S may be a range of one or any two of 40, 42, 44, 46, 48, 50, 52, 54, 56, 58, 60, 62, 64, 66, 68, 70. The present application has found that when S is further selected to be 40≤S≤75, the internal resistance of the secondary battery obtained is lower and the cycle stability is better, and the risk of gas generation during the cycle is also lower.
[0049] In one embodiment, 2≤σ≤10.
[0050] It should be noted that the oxygen content of the hollow graphene roll is obtained by referring to the Fourier transform infrared spectrometer test of GB / T21186-2007. Specifically, the oxygen content can be obtained by comparing the vibration peak intensities of different carbon and oxygen functional groups.
[0051] The oxygen content of the hollow graphene roll will affect the dispersion uniformity of lithium iron manganese phosphate inside the hollow graphene roll. When the oxygen content is within the above range, it can not only enhance the dispersion uniformity of lithium iron manganese phosphate dispersed inside the hollow graphene roll, but also enhance the chemical bonding ability between the two, thereby improving the stability of the positive electrode material and thereby improving the overall performance of the secondary battery.
[0052] Exemplarily, the σ may be any point value or any two point range value in the range of 2≤σ≤10, for example, σ may be 2, 3, 4, 5, 6, 7, 8, 9, 10, etc.
[0053] In one embodiment, 2.5≤σ≤3.5. For example, σ may be a range value of one or any two of 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5. The present application has found that when σ is further selected to be 2.5≤σ≤3.5, when the obtained positive electrode material is applied to the preparation of a secondary battery, the obtained secondary battery has better high temperature storage stability and better high and low temperature cycle performance.
[0054] In one embodiment, the pore size of the positive electrode material is 1-280 nm.
[0055] It should be noted that the pore size of the positive electrode material is obtained by measuring the pore size distribution and porosity of solid materials by mercury injection and gas adsorption methods with reference to GB / T 21650.2-2008.
[0056] The pore size distribution of the positive electrode material is critical to the transmission and diffusion of lithium ions. The pore size distribution within a suitable range can make the positive electrode material have excellent ion conductivity. The present application found that when the pore size of the positive electrode material is further selected to be 1 to 280 nm and applied to the preparation of secondary batteries, the internal resistance of the secondary battery obtained is lower and the cycle gas production is less.
[0057] Exemplarily, the pore size of the positive electrode material can be any point value or any two points in the range of 1 to 280 nm, for example, 01 nm, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, etc.
[0058] In one embodiment, the mass ratio of the hollow graphene roll to the lithium iron manganese phosphate is hollow graphene roll: lithium iron manganese phosphate = 1: (9-99).
[0059] It should be noted that the testing method for the quality of the hollow graphene roll and lithium iron manganese phosphate in the positive electrode material is obtained by thermal reference GB / T27761-2011 thermogravimetric analysis test (TG / DSC), specifically, using an air atmosphere and utilizing the difference in decomposition temperature of the hollow graphene roll and the lithium iron manganese phosphate material in the air to obtain the mass ratio of the two.
[0060] The research in this application found that the mass ratio of hollow graphene rolls and lithium iron manganese phosphate not only affects the chemical interaction between the two, but also affects the stability during the cycle process, and also affects the ionic conductivity and electronic conductivity of the positive electrode material. When the mass ratio of the two is further selected to be within the above range, when the obtained positive electrode material is used in the preparation of secondary batteries, the obtained secondary batteries have excellent comprehensive effects.
[0061] Exemplarily, the mass ratio of the hollow graphene roll and lithium iron manganese phosphate can be any point value in the range of 1:(9-99) or any two point range values, such as 1:9, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55, 1:60, 1:65, 1:70, 1:75, 1:80, 1:85, 1:90, 1:95, 1:99, etc.
[0062] In one embodiment, the thickness of the hollow graphene roll is 1-10 nm.
[0063] It should be noted that the thickness of the graphene roll is obtained by atomic force microscopy (AFM) testing.
[0064] The thickness of the hollow graphene roll will affect the ionic conductivity and electronic conductivity of the positive electrode material. When the thickness of the hollow graphene roll is further selected to be 1 to 10 nm, the internal resistance of the obtained secondary battery is lower and the cycle performance is better.
[0065] Exemplarily, the thickness of the hollow graphene roll may be any point value or any two points in the range of 1 to 10 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc.
[0066] In one embodiment, the lithium manganese iron phosphate satisfies 0.7 μm≤Dv50≤1.2 μm.
[0067] In one embodiment, the lithium manganese iron phosphate satisfies 0.2 μm≤Dv10≤0.3 μm.
[0068] In one embodiment, the lithium manganese iron phosphate satisfies 10 μm≤Dv90≤20 μm.
[0069] It should be noted that the Dv50, Dv10 and Dv90 of lithium manganese iron phosphate are obtained by testing with a laser particle size analyzer.
[0070] The research in this application found that the Dv50, Dv10 and Dv90 of lithium iron manganese phosphate will not only affect its dispersion uniformity in the hollow graphene roll, but also affect its interaction with the hollow graphene roll and the ionic conductivity and electronic conductivity of the obtained positive electrode material. When the Dv50, Dv10 and Dv90 of lithium iron manganese phosphate are further selected to be within the above-mentioned ranges, the comprehensive performance of the secondary battery prepared with the obtained positive electrode material is better.
[0071] In one embodiment, the method for preparing the positive electrode material comprises the following steps:
[0072] (1) adding lithium manganese iron phosphate to a N,N-dimethylformamide (DMF) solution of graphene oxide and stirring, followed by ultrasonication to obtain a dispersion;
[0073] (2) heating and stirring the dispersion, then keeping it warm, and then freezing it in liquid nitrogen to obtain a block;
[0074] (3) The block is placed in an inert gas environment for heat preservation treatment, and after the heat preservation treatment, it is ground to obtain a positive electrode material.
[0075] In the preparation process of the positive electrode material, the present application has no particular restrictions on the state of the raw material graphene oxide, such as powder, flake, etc. At the same time, the raw material graphene oxide of the present application can be achieved by conventional synthesis methods in the art, such as Brodie method, Staudenmaier method and Hummers method. For example, when the Hummers method is used, the method does not require an external heat source, avoids the temperature control process, ensures the safety of the preparation process, and can also significantly reduce the cost of production, which is suitable for large-scale production.
[0076] In addition, in addition to the difference in oxygen content in the raw material graphene oxide rolls used for the hollow graphene rolls with different oxygen contents prepared in this application, the graphene oxide with high oxygen content can also be reduced after being kept warm in step (2) and before being frozen in liquid nitrogen; specifically, at least one of the synthesis methods of chemical reduction and thermal reduction can be used. Among them, the reducing agent used in the chemical reduction method includes chemical reducing agents such as hydrazine hydrate, vitamin C, and hydroiodic acid; the temperature range of the thermal reduction method is 400-600°C, the heating rate is 5-20°C / min, and the insulation time is 180-240min. For example, an 80% mass percent hydrazine hydrate solution can be used to reduce graphene oxide, wherein the mass ratio of hydrazine hydrate to graphene oxide is (3-15):1.
[0077] At the same time, since the raw material graphene oxide in the hollow graphene roll or the graphene oxide in the preparation process of the positive electrode material may be obtained through different reactions, the hollow graphene roll in the positive electrode material after the reaction also contains various oxygen-containing functional groups, such as at least one of carboxyl, hydroxyl, carbonyl, epoxy, and ether groups.
[0078] This application does not specifically limit the number of layers of the raw material graphene oxide, for example, it can be any point value within the range of 1 to 10 layers or any two point range value. This application study found that the number of graphene oxide layers has a certain influence on the yield of hollow graphene rolls. When the number of graphene oxide layers is relatively low, the energy barrier required to overcome bending and winding when preparing hollow graphene rolls is smaller, making it easier to obtain hollow graphene rolls, improve the preparation efficiency of positive electrode materials, and reduce energy losses. At the same time, the number of graphene oxide layers will also have a certain influence on the thickness of the hollow graphene rolls.
[0079] This application does not specifically limit the sheet diameter of the raw material graphene oxide, for example, it can be any point value or any two point range value within the range of 0.2 to 50 μm. This application study found that the choice of sheet diameter not only affects the inner diameter of the hollow graphene roll in the positive electrode material, but also has a certain impact on the specific surface area of the positive electrode material; at the same time, the choice of sheet diameter will also affect the difficulty of bending and winding the graphene oxide. When the sheet diameter increases relatively, the difficulty of curling will decrease relatively.
[0080] In one embodiment, graphene oxide and lithium manganese iron phosphate are dried at 45-55° C. for 10-14 hours before use.
[0081] In one embodiment, in step (1), the mass concentration of graphene oxide in the DMF solution of graphene oxide is (1-3) mg / mL.
[0082] In one embodiment, in step (1), the stirring time is 20 to 40 minutes, and the ultrasonic time is 5 to 15 minutes.
[0083] In one embodiment, in step (2), the temperature of heating and stirring is 65-75° C. and the time of heating and stirring is 25-35 min.
[0084] In one embodiment, in step (2), the insulation temperature is 75-85° C., and the insulation time is 8-12 minutes.
[0085] In one embodiment, in step (3), the temperature of the heat preservation treatment is 530-570° C., and the time of the heat preservation treatment is 160-200 min.
[0086] It should be noted that the above only provides a method for preparing hollow graphene rolls, namely, freeze-drying method, and it can also be prepared by conventional methods in the art, such as chemical vapor deposition, electrospinning, liquid spinning, etc. And the present application has found that the pore size and specific surface area of the positive electrode material can be regulated by selecting different preparation methods of hollow graphene rolls and controlling parameters in the preparation process.
[0087] In one embodiment of the present application, the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, and the positive electrode active material layer includes the above-mentioned positive electrode material.
[0088] In one embodiment, the positive electrode active material layer further includes a conductive agent and a binder.
[0089] This application has no special requirements for the conductive agent and the binder, and any known conductive agent and binder can be used. Exemplarily, the conductive agent includes at least one of carbon nanotubes (CNT), conductive carbon black (SP), conductive graphite, Ketjen black (ECP), acetylene black, and graphene; the binder includes at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTFE), polyethylene glycol (PEG), polyvinyl acetate (PVAc), polyacrylonitrile (PAN), and polyimide (PI).
[0090] In one embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active material. The present application has no limitation on the negative electrode active material, and any known negative electrode active material can be used.
[0091] In one embodiment, the electrolyte includes an organic solvent, a lithium salt and an additive. The present application has no limitation on the organic solvent, lithium salt and additive in the electrolyte, and any known organic solvent, lithium salt and additive can be used.
[0092] Exemplarily, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate; the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide; and the additive includes at least one of a film-forming additive and a flame retardant additive.
[0093] In one embodiment, the separator of the secondary battery is disposed between the positive electrode and the negative electrode.
[0094] Example 1
[0095] The present invention provides a positive electrode material and a secondary battery. The preparation method of the positive electrode material and the secondary battery comprises the following steps:
[0096] (1) Preparation of positive electrode materials
[0097] S1. Take a certain amount of graphene oxide powder (with an average sheet diameter of 25 μm and 1 layer, obtained by oxidation using the Hummers method) and lithium iron manganese phosphate powder and bake them in an oven at a temperature of 80° C. for 12 h.
[0098] S2, the baked graphene oxide powder was dissolved in DMF solvent, and ultrasonic stirring in a water bath for 15 min was performed to obtain a uniformly dispersed graphene oxide solution with a concentration of 2 mg / mL, to which 20 times the mass (in terms of graphene oxide powder) of lithium iron manganese phosphate powder was added, and the dispersion was magnetically stirred for 30 min, and then ultrasonic stirring in a water bath for 10 min was performed to obtain a dispersion;
[0099] S3, placing the dispersion in a magnetic stirring water bath at 70°C, heating and stirring for 30 minutes, then raising the temperature to 80°C and keeping warm for 10 minutes;
[0100] S4, quickly transfer the dispersion after the insulation in S3 into liquid nitrogen, and after the dispersion is completely frozen, transfer it to a freeze dryer and freeze-dry it for 24 hours to obtain a block;
[0101] S5, placing the block in a tubular furnace, filling it with Ar gas as a protective gas, heating at a rate of 5°C / min, heating to 550°C and then keeping the temperature for 180min;
[0102] S6. After the heat preservation is completed, grind to obtain the positive electrode material.
[0103] (2) Preparation of positive electrode sheet
[0104] The positive electrode material, PVDF dispersant and acetylene black (SP) are evenly mixed in a mass ratio of 96:2:2, and NMP solvent is added thereto for dispersion and continuous stirring. After the dispersion forms a black slurry state with a certain viscosity, it is evenly coated on both sides of the carbon-coated aluminum foil, and then baked, rolled, die-cut and slit to obtain the positive electrode sheet.
[0105] (3) Preparation of negative electrode sheet
[0106] The negative electrode active material artificial graphite, the conductive agent acetylene black (SP) and the binder SBR are mixed evenly in a mass ratio of 96:2:2, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the copper foil, and then baked, rolled, die-cut and slit to obtain the negative electrode sheet.
[0107] (4) Production of secondary batteries
[0108] The prepared positive electrode sheet, separator and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets. The bare battery cell is obtained by winding and hot pressing. After that, the assembled square aluminum battery is obtained through ultrasonic welding and other processes. The battery is placed in an oven at 110±5℃ and baked for 24 hours. After that, a secondary battery is obtained through a series of processes such as liquid injection, formation, aging and capacity division.
[0109] Embodiment 2-3
[0110] Embodiments 2 to 3 provide a positive electrode material and a secondary battery. The difference between the positive electrode material and the embodiment 1 is that the inner diameter of the hollow graphene roll, the oxygen content and the specific surface area of the positive electrode material are changed by adjusting the sheet diameter, the number of layers of graphene oxide, and the parameters in the redox process and the positive electrode material preparation process.
[0111] Embodiments 4 to 7
[0112] Embodiments 4 to 7 provide a positive electrode material and a secondary battery. The difference between the positive electrode material and embodiment 1 is that the inner diameter of the hollow graphene roll is changed by adjusting the sheet diameter and the number of layers of graphene oxide.
[0113] Embodiments 8 to 11
[0114] Embodiments 8 to 11 provide a positive electrode material and a secondary battery. The difference between the positive electrode material and the embodiment 1 is that the specific surface area of the positive electrode material is changed by adjusting the parameters in the preparation process of the positive electrode material.
[0115] Embodiments 12 to 15
[0116] Embodiments 12 to 15 provide a positive electrode material and a secondary battery. The difference between the positive electrode material and embodiment 1 is that the oxygen content of the hollow graphene roll is changed by adjusting the redox process of graphene oxide and the preparation process of the positive electrode material.
[0117] Embodiments 16 to 17
[0118] Embodiments 16 to 17 provide a positive electrode material and a secondary battery. The difference between the positive electrode material and the embodiment 1 is that the pore size of the positive electrode material is changed by adjusting the parameters in the preparation process of the positive electrode material.
[0119] Embodiments 18 to 19
[0120] Embodiments 18 to 19 provide a positive electrode material and a secondary battery. The difference between the positive electrode material and embodiment 1 is that the thickness of the hollow graphene roll is changed by adjusting the sheet diameter and the number of layers of graphene oxide.
[0121] Embodiment 20-21
[0122] Embodiments 20 to 21 provide a positive electrode material and a secondary battery. The difference between the positive electrode material and the embodiment 1 is that the mass ratio of the hollow graphene roll and the lithium iron manganese phosphate is changed by adjusting the amount of graphene oxide and lithium iron manganese phosphate added during the preparation of the positive electrode material.
[0123] Embodiments 22-23
[0124] Embodiments 22 to 23 provide a positive electrode material and a secondary battery. The difference between the positive electrode material and that of Embodiment 1 is that the changes in Dv10, Dv50 and Dv90 of the lithium manganese iron phosphate are achieved by adjusting the grinding and screening of the lithium manganese iron phosphate.
[0125] Comparative Example 1
[0126] Comparative Example 1 provides a positive electrode material and a secondary battery. The difference between the secondary battery and Example 1 is that lithium manganese iron phosphate is used alone and is not dispersed in a hollow graphene roll.
[0127] Comparative Example 2
[0128] Comparative Example 2 provides a positive electrode material and a secondary battery. The difference between the secondary battery and Example 1 is that the lithium manganese iron phosphate particles coated with ordinary carbon purchased on the market are used.
[0129] The average inner diameter, oxygen content, thickness of the hollow graphene rolls in the positive electrode materials in the embodiments and comparative examples, Dv10, Dv50 and Dv90 of lithium manganese iron phosphate, and the specific surface area and pore size parameters of the positive electrode materials are shown in Table 1.
[0130] Table 1
[0131]
[0132]
[0133] The cycle performance, internal resistance and stability of the secondary batteries prepared in the examples and comparative examples are shown in Table 2; wherein the test method comprises the following steps:
[0134] (1) Room temperature DCR test: At 25±2°C, the secondary battery is charged to 4.25V at 0.33C constant current and constant voltage, then discharged at 0.33C capacity for 90min, adjusted to 50% SOC, and then discharged at 3C constant current pulse for 10s and then charged for 10s. Calculate DCR = (voltage before pulse discharge - voltage after pulse discharge) / discharge current × 1000;
[0135] (2) Normal temperature cycle performance test: At 25±2℃, the secondary battery is cycled using the FC / 1C fast charge system for 30 minutes, with a cycle voltage range of 2.5-4.25V. At the same time, the number of cycles at which the battery capacity retention rate is 80% is recorded. Capacity retention rate of a certain cycle (SOH) = discharge capacity of a certain cycle / discharge capacity of the first cycle × 100%;
[0136] (3) High temperature cycle performance test: At 45±2℃, the secondary battery is cycled using the FC / 1C fast charge system for 30 minutes, with a cycle voltage range of 2.5 to 4.25V. At the same time, the number of cycles at which the battery capacity retention rate is 80% is recorded. Capacity retention rate of a certain cycle (SOH) = discharge capacity of a certain cycle / discharge capacity of the first cycle × 100%;
[0137] (4) High temperature storage test: Charge the secondary battery at 25±2℃ with a constant current of 0.33C to 4.25V, and then charge it at a constant voltage of 4.25V until the current is less than 0.05C, so that it is in a fully charged state of 4.25V. Test the battery capacity C0 before storage; then place the fully charged battery in a 60±2℃ oven, and charge it to 4.25V at a current of 0.1C every 24h. After 90 days, take out the battery, and immediately test its capacity after storage and record it as C1. Capacity retention rate (SOH) = C1 / C0×100%;
[0138] (5) High temperature cycle gas generation test: At 45±2°C, the secondary battery is subjected to a charge and discharge cycle test at a charge and discharge rate of 0.33C / 0.33C in the range of 2.5 to 4.25V. The internal pressure of the battery is recorded every 10 minutes. After 60 days, the maximum internal pressure during the final battery cycle is recorded.
[0139] Table 2
[0140]
[0141]
[0142] It can be seen from Table 2 that when the prepared positive electrode material is applied to the preparation of a secondary battery using the technical solution of the present application, the obtained secondary battery has low internal resistance, excellent cyclability and high temperature stability, and low risk of gas generation during the cycle; specifically, the DCR of the obtained secondary battery is below 1.28 mΩ, the number of 80% SOH cycles at 25°C is above 1550 cycles, the number of 80% SOH cycles at 45°C is above 600 cycles, the storage SOH at 60°C is above 84.68%, and the cyclic internal pressure at 45°C is below 0.098 MPa; at the same time, it can be seen from the embodiments that when the positive electrode material is further selected to satisfy 15≤Y≤500, the comprehensive effect of the obtained secondary battery is better.
[0143] It can be seen from the examples and comparative examples 1 to 2 that when the hollow graphene roll is not added or the coating is not performed in the form of a hollow graphene roll, the overall performance of the obtained secondary battery is significantly reduced.
[0144] In addition, the hollow graphene rolls and common flake graphene prepared in this application were observed, and the electron microscope images were as follows: Figure 1 , Figure 2 As shown, from Figure 1 It can be seen that the hollow graphene roll prepared in the present application forms a curled structure with hollow gaps inside.
[0145] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes a hollow graphene roll and lithium manganese iron phosphate, and the lithium manganese iron phosphate is dispersed inside the hollow graphene roll.
2. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies: 11≤Y≤495; Where, Y = d × S / σ; d μm is the average inner diameter of the hollow graphene roll; Sm 2 / g is the specific surface area of the positive electrode material; σ% is the oxygen content of the hollow graphene roll.
3. The positive electrode material according to claim 1, characterized in that At least one of the following is met: a, 1≤d≤15; b. 10≤S≤250; c. 2≤σ≤10.
4. The positive electrode material according to claim 1, characterized in that The pore diameter of the positive electrode material is 1 to 280 nm.
5. The positive electrode material according to claim 1, characterized in that The mass ratio of the hollow graphene roll to the lithium iron manganese phosphate is hollow graphene roll: lithium iron manganese phosphate = 1: (9-99).
6. The positive electrode material according to claim 1, characterized in that The thickness of the hollow graphene roll is 1 to 10 nm.
7. The positive electrode material according to claim 1, characterized in that The lithium iron manganese phosphate satisfies: 0.7 μm≤Dv50≤1.2 μm.
8. The positive electrode material according to claim 1, characterized in that The lithium manganese iron phosphate satisfies at least one of the following: d.0.2μm≤Dv10≤0.3μm; e.10μm≤Dv90≤20μm.
9. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes the positive electrode material according to any one of claims 1 to 8.
10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.
